Alpha synuclein co-pathology is associated with accelerated amyloid-driven tau accumulation in Alzheimer’s disease - Nicolai Franzmeier; Sebastian Niclas Roemer-Cassiano; Alexander Maximilian Bernhardt; Amir Dehsarvi; Anna Dewenter; Anna Steward; Davina Biel; Lukas Frontzkowski; Zeyu Zhu; Johannes Gnörich; Julia Pescoller; Fabian Wagner; et al. (Molecular Neurodegeneration)
Abstract Background Aggregated alpha-Synuclein (αSyn) is a hallmark pathology in Parkinson’s disease but also one of the most common co-pathologies in Alzheimer’s disease (AD). Preclinical studies suggest that αSyn can exacerbate tau aggregation, implying that αSyn co-pathology may specifically contribute to the Aβ-induced aggregation of tau that drives neurodegeneration and cognitive decline in AD. To investigate this, we combined a novel CSF-based seed-amplification assay (SAA) to determine αSyn positivity with amyloid- and tau-PET neuroimaging in a large cohort ranging from cognitively normal individuals to those with dementia, examining whether αSyn co-pathology accelerates Aβ-driven tau accumulation and cognitive decline. Methods In 284 Aβ-positive and 308 Aβ-negative subjects, we employed amyloid-PET, Flortaucipir tau-PET, and a CSF-based αSyn seed-amplification assay (SAA) to detect in vivo αSyn aggregation. CSF p-tau181 measures were available for 384 subjects to assess earliest tau abnormalities. A subset of 155 Aβ-positive and 135 Aβ-negative subjects underwent longitudinal tau-PET over approximately 2.5 years. Using linear regression models, we analyzed whether αSyn SAA positivity was linked to stronger Aβ-related increases in baseline fluid and PET tau biomarkers, faster Aβ-driven tau-PET increase, and more rapid cognitive decline. Results αSyn SAA positivity was more common in Aβ + vs. Aβ- subjects and increased with clinical severity (p < 0.001). Most importantly, αSyn positivity was also associated with greater amyloid-associated CSF p-tau181 increases (p = 0.005) and higher tau-PET levels in AD-typical brain regions (p = 0.006). Longitudinal analyses confirmed further that αSyn positivity was associated with faster amyloid-related tau accumulation (p = 0.029) and accelerated amyloid-related cognitive decline, potentially driven driven by stronger tau pathology. Conclusions Our findings suggest that αSyn co-pathology, detectable via CSF-based SAAs, is more prevalent in advanced AD and contributes to the development of aggregated tau pathology thereby driving faster cognitive decline. This highlights that a-Syn co-pathology may specifically accelerate amyloid-driven tau pathophysiology in AD, underscoring the need to consider αSyn in AD research and treatment strategies.